Cardiomyopathy Induced by Artificial Heart Stimulation - Galvão Filho, Silas dos Santos (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
With the advent of cardiac pacemakers more than 60 years ago, the era of artificial cardiac pacing began, which changed the natural history of symptomatic bradycardias, significantly increasing the survival especially of patients with complete atrioventricular block.